Hybrid Conversion of 5‐Hydroxymethylfurfural to 5‐Aminomethyl‐2‐furancarboxylic acid: Toward New Bio‐sourced Polymers. Issue 1 (26th November 2020) - Lancien, Antoine; Wojcieszak, Robert; Cuvelier, Eric; Duban, Matthieu; Dhulster, Pascal; Paul, Sébastien; Dumeignil, Franck; Froidevaux, Renato; Heuson, Egon
Abstract: Hybrid catalysis, which combines chemo‐ and biocatalytic benefits, is an efficient way to address green chemistry principles. 5 ‐Hydroxymethylfurfural (HMF) is a versatile building block in numerous industrial applications. To date, few studies have described the production of its amine derivatives and their polymers. Finding a good methodology to directly transform HMF to 5 ‐aminomethyl‐ 2 ‐furancarboxylic acid (AMFC) therefore represents an important challenge. After selecting the best oxidation catalyst for HMF conversion to 5 ‐aldehyde‐ 2 ‐furancarboxylic acid and immobilizing a transaminase onto a solid carrier, we implemented the first one‐pot/two‐steps hybrid catalytic process to produce AMFC (77 % yield); this is the most efficient AMFC catalytic production method from HMF reported to date. This process also produced 2, 5 ‐furandicarboxylic acid (21 % yield) as a major secondary product that can be applied to polymer syntheses such as polyethylene furanoate. Herein, we report a novel way to access new biosourced polymers based on HMF oxidized and aminated derivatives. Abstract : Hybrid catalysis : 5‐Hydroxymethylfurfural is one of the main building blocks that can be easily obtained from biomass. Among its many possible transformations, furfurylamines have been little explored, probably due to their difficult synthesis which generally requires difficult conditions. This study presents a hybrid catalytic system combining a metal nanoparticle and an enzyme to efficiently produce 5‐aminomethyl‐2‐furancarboxylic acid under mild conditions.